Gender and Land Administration : Issues and Responses - Stanley, Victoria (World Bank, Washington, DC, 2014)
Land rights for women are important to women's overall role in the household economy. In most Europe and Central Asia (ECA) countries, women have equal rights to land by law, but practice varies widely across the region. Improving gender outcomes in land administration is therefore related more to education and the need to change norms and habits than it is to a specific legislative problem. Access to gender-disaggregated data and the inclusion of gender-specific messages in public awareness campaigns, training, and education can have a significant impact. Simple steps to protect and promote women's property rights are easily integrated into project activities, often at low cost. Finally, more research is needed on the gender impacts of access to credit and ways to improve women's access to credit.